Functional Properties of Lupinus angustifolius Seed Protein Isolates - Antonio Hilario Lara-Rivera; Pedro García-Alamilla; Laura Mercedes Lagunes-Gálvez; Ramón Rodríguez Macias; Pedro M. García López; Juan Francisco Zamora Natera (Journal of Food Quality)
Protein isolates prepared by alkaline solubilization followed by isoelectric precipitation and freeze-drying from six varieties of Lupinus angustifolius (Haags Blaue, Sonate, Probor, Borlu, Boregine, and Boruta) grown in Mexico were evaluated for functional properties: nitrogen solubility, water-holding capacity (WHC), oil holding capacity (OHC), emulsion activity index (EAI), emulsion stability index (ESI), foaming capacity (FC), foam stability (FS), and gelling minimum concentration (GMC). The nitrogen solubility values, WHC, OHC, and FC did not show significant differences between the protein isolates. The solubility of the isolates was minimal at pH of 4.0 and 5.0 while the regions of maximum solubility were found at pH of 2.0 and 10.0. There were significant differences in EAI and ESI depending on the varieties used. The isolates of the Boregine and Borlu varieties showed the highest EAI with 29.3 and 28.3 m2 g−1, respectively, while the lowest index was recorded in the isolate obtained from the Sonate variety (24.6 m2 g−1). Like solubility, these indices also increased at both extremes of pH evaluated; both properties were minimal in the isoelectric pH range (4.0 to 5.0).